Investigation of the relationship between mean platelet volume and obstructive sleep apnea syndrome. Issue 4 (2013) - Erden, Ersin Şükrü; Yengil, Erhan; Tuncel, Ertan; Bilgiç, Hatice Kayım; Demirköse, Mesut; Motor, Sedat; Genç, Sebahat
No abstract available